Pengaruh masa kerja, lingkungan kerja dan employee engagement terhadap kinerja karyawan PT Surya Pamenang kediri - Sulton Nugroho; Nur Aidya Fajariah; Nur Hidayati (Jurnal Bisnis Islam dan Kewirausahaan, 2022)
This study aims to determine: (1) the effect of tenure on employee performance, (2) the influence of the work environment on employee performance, (3) the effect of employee engagement on employee performance (4) the effect of tenure, work environment and employee engagement on employee performance. This type of research uses a quantitative approach. The sample of this research is employees of electrical engineering PT. Surya Pamenang, Kediri as many as 80 respondents. The sampling technique used was purposive sampling. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of the study at a significance level of 5% indicate that: (1) there is a partial and significant effect of tenure on employee performance. (2) there is a partial and significant effect of the work environment on employee performance. (3) there is a partial and significant effect of Employee Engagement on Employee Performance.. (4) there is an effect of working period, work environment and employee engagement simultaneously on employee performance